Affect in Secondary Students' Reading as Revealed by their Emotional Responses in Retrospective Miscue Analysis - Liwanag, Maria Perpetua Socorro U. (The University of Arizona., 2006)
The purpose of this study was to explore and understand the emotional responses of selected high school readers when they engage in retrospective miscue analysis.Several data sets were collected through audio and video taping of interviews, readings, and individual and group sessions. Analysis of the data involved the use of In Depth procedure of miscue analysis to examine readers' meaning construction, grammatical patterns, and word substitution similarities. Results from the miscue analysis sessions were used to engage the students in retrospective miscue analysis (RMA). RMA consisted of engaging readers to reflect and evaluate the reading process and strategies by analyzing their miscues. Their emotional responses during the RMA sessions were examined and analyzed to describe patterns in readers' revalued voices. Martin and White's (2005) appraisal theory was used to analyze student's emotional responses. Appraisal theory is based on Halliday's systemic functional linguistic view of language.Research findings indicated that readers became adept at articulating their own strategies, fine tuned their own affective stance about reading and used what they know about miscues and reading to better themselves as readers. Their emotional responses towards reading also changed over time as students began to use linguistic resources to agree, disagree, critique, and position their listeners to their own assessments and adapted their own revalued voice about who they are as readers. Readers' miscues also showed that they began to focus more on making meaning, thus improving their reading.